Culture Diversity in Indonesia ELT Textbook - Gayypov, Hudaynazar; Rahmawan, Andi Dian; Barnaba, Hengki Yudha (Universitas PGRI Yogyakarta, 2024)
This study analyzes cultural diversity representation in the newest mandated English textbook of the Merdeka curriculum for seventh grade. The researcher uses Cortazzi and Jin's theory of cultural representation, dividing the representation into three cultures: source, target, and international. This research was conducted using a qualitative descriptive method, and the whole book is analyzed without exception. From this research, the researcher found that a set of pilot characters has an important role in delivering the materials. The pilot characters come from various backgrounds from various places in Indonesia. Moreover, they also have different hobbies that will be the main highlight of this research. First, it is found that there is a complex representation of source culture, or Indonesian culture, where there are people, lifestyles, culinary, and traditional representations of culture. Then, the target culture, or the English native language country, is represented once, and finally, the international culture presents lifestyle and culinary aspects. Secondly, this textbook presents an imbalanced cultural diversity in delivering its material. Therefore, the researcher hopes this research could raise the awareness of cultural diversity as it is important for the students to be exposed to many different cultural aspects.